Effects of Refertilization on Growth and Nutrition of Lodgepole Pine (Pinus contorta Dougl.) Planted on a Minerotrophic Peatland in Central Newfoundland, Canada - WELLS, E. D.; MILLER, H. G. (Forestry, 1994)
A plantation of lodgepole pine ( Pinus contorta Dougl.), which was established in 1973 on a ditched minerotrophic fen at planting spacings of 1.2 m, 1.8 m, and 2.4 m, was refertilized in 1985 with control, P, PK and NPK treatments consisting of 60 kg ha−1 phosphorus, 100 kg ha−1 potassium and 200 kg ha−1 nitrogen. Although each seedling had been spot-fertilized in 1973 with a mixture of 71 g urea, 99 g ground rock phosphate and 41 g potassium sulphate, height and needle nutrient assessments of the plantation in 1984 indicated poor growth, low concentrations of needle nitrogen (1.26 per cent) and possible deficiency levels of needle phosphorus (0.10 per cent) and potassium (0.36 per cent). Between 1985 and 1991, height and diameter growth increased significantly in all refertilization treatments. Growth response was greatest in the PK treatment and least in the P treatment. Needle weights, determined from 1987 to 1991, did not respond uniformly to any of the refertilization treatments. Needle concentrations of phosphorus increased to levels between 0.20 per cent and 0.23 per cent following refertilization with P, PK, and NPK, but by 1988 had decreased to about 0.14 per cent. Needle concentrations of potassium also increased sharply to 0.60 per cent in 1985 following refertilization with PK and NPK, but by 1988 had decreased to levels between 0.35 per cent and 0.45 per cent. Similarly, needle nitrogen concentrations increased to 1.84 per cent in 1985 following refertilization with NPK, then decreased to levels between 1.20 per cent and 1.33 per cent in 1986 and remained at those levels each year thereafter. Although needle nutrient levels fell sharply following an initial peak after refertilization, height and diameter growth did not decrease significantly, especially in the PK treatment, suggesting that nutrient levels remained adequate for optimum growth.